Peak-amplitude detector for sinusoidal signals - Pookaiyaudom, S.; Watanachaiprateep, C.; Dejhan, K. (My University, 1979)
A circuit technique is proposed for detecting the peak amplitude of a sinusoidal signal using Pythagoras's law without requiring a simultaneous equal-amplitude quadrature signal. The number of four-quadrant multipliers required is only two.© 1979, The Institution of Electrical Engineers. All rights reserved.
Keywords: Detector circuits